Electroanalytical determination of carbendazim and fenamiphos in natural waters using a diamond electrode - Franca, Rafaela F.; de Oliveira, Hueder Paulo M.; Pedrosa, Valber A. [UNESP]; Codognoto, Lucia (Elsevier B.V. Sa, 2012)
In this study, a method for electroanalytical determination of carbendazim (CBZ) and fenamiphos (FNP) in natural and spiked water was developed using square wave voltammetly in Na2HPO4 0.1 mol L-1 as supporting electrolyte. The calibration curve for carbendazim detection presented good linearity in the concentration range of 0.50 to 15.0 mu M, with a sensitivity of 0.080 A/mol L-1 and a linearity of 0.998. The oxidation of fenamiphos on BDD electrode shows a dynamic range of concentration of 0.5 to 25.0 mu M and sensibility of 0.14 A/mol L-1. The recovery experiments showed values between 70 and 100% for spiked samples thus indicating the feasibility of the electroanalytical methodology to quantify CBZ and FNP in pure or natural waters. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Pesticide; Diamond electrode; Carbendazim; Fenamiphos; Water analysis